Does social participation improve self-rated health in the older population? A quasi-experimental intervention study - Ichida, Yukinobu; Hirai, Hiroshi; Kondo, Katsunori; Kawachi, Ichiro; Takeda, Tokunori; Endo, Hideki (Social science & medicine (1982), 2013)
Social participation has been linked to healthy aging and the maintenance of functional independence in older individuals. However, causality remains tenuous because of the strong possibility of reverse causation (healthy individuals selectively participate in social activities). We describe a quasi-experimental intervention in one municipality of Japan designed to boost social participation as a way of preventing long-term disability in senior citizens through the creation of ‘salons’ (or community centers). In this quasi-experimental intervention study, we compared 158 participants with 1391 non-participants in salon programs, and examined the effect of participation in the salon programs on self-rated health. We conducted surveys of community residents both before (in 2006) and after (in 2008) the opening of the salons. Even with a pre/post survey design, our study could be subject to reverse causation and confounding bias. We therefore utilized an instrumental variable estimation strategy, using the inverse of the distance between each resident's dwelling and the nearest salon as the instrument. After controlling for self-rated health, age, sex, equivalized income in 2006, and reverse causation, we observed significant correlations between participation in the salon programs and self-rated health in 2008. Our analyses suggest that participation in the newly-opened community salon was associated with a significant improvement in self-rated health over time. The odds ratio of participation in the salon programs for reporting excellent or good self-rated health in 2008 was 2.52 (95% CI 2.27–2.79). Our study provides novel empirical support for the notion that investing in community infrastructure to boost the social participation of communities may help promote healthy aging. •Social participation is linked to improved health, yet causality remains unclear due to possibility of reverse causation.•We utilized an instrumental variable estimation strategy to reduce the effect of reverse causation.•Findings suggest that participation in the community salon improves self-rated health.